2020
DOI: 10.1159/000510953
|View full text |Cite
|
Sign up to set email alerts
|

Does Asthma Increase the Mortality of Patients with COVID-19?: A Systematic Review and Meta-Analysis

Abstract: The purpose of this systematic review and meta-analysis was to explore the literature and collate data comparing the mortality of coronavirus disease 2019 (COVID-19) patients with and without asthma. The databases PubMed, Scopus, Embase, Google Scholar, and medRxiv.org were searched for studies comparing the clinical outcomes of asthmatic patients with those of nonasthmatic patients diagnosed with COVID-19. Mortality data were summarized using the Mantel-Haenszel OR with 95% CI in a random-effects model. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 24 publications
5
53
0
3
Order By: Relevance
“…Since the outbreak there has been much debate about the extent to which asthma is a risk factor for susceptibility to SARS-CoV-2 infection or severe disease progression of COVID-19, and results of studies addressing these issues vary substantially [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Recent large studies and meta-analyses however suggest that asthma patients in general may not be at risk for severe COVID-19, which may be due to a potential protective effect of type 2 inflammation [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak there has been much debate about the extent to which asthma is a risk factor for susceptibility to SARS-CoV-2 infection or severe disease progression of COVID-19, and results of studies addressing these issues vary substantially [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. Recent large studies and meta-analyses however suggest that asthma patients in general may not be at risk for severe COVID-19, which may be due to a potential protective effect of type 2 inflammation [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%
“…According to rank (with a cut off score 4), the enriched known or reported comorbid conditions or long-term complications are lupus erythematosus (Rank-1) [100], depressive disorder / mental depression (Rank-2) [30, 101], hepatitis C (Rank-3) [102], breast cancer (Rank-4) [75], arthritis (Rank-5) [103], asthma (Rank-6) [10, 77], liver cancer (Rank-6) [78], tuberculosis (Rank-7) [104, 105], diabetes (Rank-8) [82], myocardial infarction (Rank-9) [35, 106], macular degeneration (Rank-9) [80], chronic kidney disease (Rank-9) [56, 57], arteriosclerosis (Rank-10) [107], ulcerative colitis (Rank-10) [108], liver cirrhosis (Rank-11) [12, 109], sepsis / septicaemia /septic shock (Rank-11) [60, 81], other autoimmune diseases (Rank-12) [49, 50], cerebrovascular accident / stroke (Rank-13) [110], congenital anemia (Rank-13) [111], COPD (Rank-13) [86], multiple myeloma (Rank-14) [112], hypertensive disease (Rank-14) [9, 113], dyslipidemia (Rank-15) [93], metabolic syndrome X (Rank-15) [51, 114], osteoporosis (Rank-16) [91], prostate cancer (Rank-17) [115], psoriasis (Rank-17) [116], leukemia (Rank-18) [117, 118], long QT syndrome (Rank-18) [119], dementia (Rank-18) [120], schizophrenia (Rank-18) [121], intellectual disability (Rank-18) [122, 123], diabetic kidney disease/ diabetic nephropathy (Rank-18) [124]etc.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis on underlying comorbid conditions in expired COVID-19 patients reveals hypertension is the most common comorbidity (46%) in COVID-19 followed by diabetes (26%), cardiovascular diseases (21%), cerebrovascular disease (13%), cancers (11%), Lung disease (11%), COPD (8%), kidney disease (7%), liver disease (3%), and asthma (3%) [9]. However, another meta-analysis suggests that asthma as a comorbid condition may not increase the mortality (OR: 0.96) [10]. Increased aspartate aminotransferase is associated with high severity and death from COVID-19 (OR: 4.48) [11] and patients with cirrhosis showed worsening liver function and increased mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies explored the prevalence of asthma among children and adults with confirmed COVID-19 infection and failed to find an increased risk of contracting the infection or of adverse outcomes among asthmatic patients 27,28 . A recent review with meta-analysis done in adults with COVID-19 (744 asthmatic and 8151 non-asthmatic) showed that the presence of asthma had no significant effect on mortality (OR=0.96 [0.70-1.30], I 2 =0%, p=0.79), duration of hospitalization, or the risk of ICU admission 29 . However, COVID-19 infection was significantly underdiagnosed during the initial months of the pandemic due to limited availability of diagnostic tests, that led most countries to recommend home isolation without testing in case of non-severe symptoms consistent with COVID-19.…”
Section: Discussionmentioning
confidence: 99%